The extracellular matrix of porcine mature oocytes: Origin, composition and presumptive roles - Pivko Juraj; Kopečný Václav; Degrouard Jeril; Fléchon Jacques E; Pavlok Antonin; Motlik Jan (Reproductive Biology and Endocrinology, 2003)
Abstract The extracellular matrix (ECM) of porcine mature oocytes was revealed by transmission electron microscopy (TEM) after treatment with tannic acid and ruthenium red. Present in the perivitelline space (PVS) and on the surface of the zona pellucida (ZP), it appeared to be composed of thin filaments and granules at the interconnections of the filaments, which were interpreted respectively as hyaluronic acid chains and bound proteoglycans. In order to determine whether this material is produced by the corona cells (the same ECM was found also on the surface of the zona pellucida and between cumulus cells) or by the oocyte itself, the synthesis of glycoproteins and glycosaminoglycans was checked by autoradiography on semi-thin and thin sections observed by light and electron microscopy. Immature oocytes within or without cumulus cells, were incubated with L [3H-] fucose or L [3H-] glucosamine – precursors respectively of glycoproteins and hyaluronic acid or hyaluronan (HA) bound to proteoglycans – for various times (with or without chase) and at different stages during in vitro maturation. In the first case, incorporation was found in both cumulus cells and ooplasm (notably in the Golgi area for 3H-fucose) and labeled material accumulated in the ECM of the PVS and of the ZP surface. Labeling in the PVS with both precursors was maximum between metaphase I (MI) and metaphase II (MII) and was partially extracted by hyaluronidase but not by neuraminidase. Tunicamycin, an inhibitor of glycoprotein synthesis, significantly decreased the amount of 3H-fucose labeled molecules in the PVS and increased the incidence of polyspermic penetration during subsequent in vivo fertilization. Since cumulus-free oocytes also secreted 3H-glucosamine containing compounds, both oocyte and cumulus cells probably contribute to the production of the ECM found in the PVS of mature oocytes. ECM and particularly its HA moiety present on both sides of the ZP may constitute a favourable factor for sperm penetration.